Physicochemical and Metal Profiles of Soils as Influenced by Crude Oil Contamination in Abraka, Delta State, Nigeria - Agbogidi, Oghenerioborue Mary; Ogbe, O.; Usen, E. N. (Journal of Science Research and Reviews, 2025)
An assessment of the physicochemical and metal profiles of soils as affected by crude oil contamination in Abraka, Delta State, Nigeria was carried out using five levels of oil treatments ( 0, 30, 60, 90 and 120 ml per 2 kg of soil). Soil samples were dried after proper missing at ambient temperature and crushed in a porcelain mortar and sieved through 2mm stainless sieve. The air dried soils were stored in polythene bags for subsequent analysis. Soils physicochemical analysis was done following the methods of the Association of Analytical of Chemist (AOAC, 2010) while the heavy metals using Atomic Absorption Spectrophotometer. The results showed that crude oil impacted soil properties variedly significant increases (P ≤ 0.05) were observed in bulk density, total pH, organic carbon, nitrogen while significant reductions were observed for phosphorous, calcium, magnesium, potassium, total porosity, electrical conductivity and hydraulic conductivity. There was however a buildup of trace metals including Cu, N, Ma, Pb, Zn, Cr and Cd. The study established that these alternatives can have great implications on plant production, yield and food security impacting human health and environment due to their toxicity, persistence and bioaccumulation potentials. The study recommends environmental monitoring and education on a regular basis.